Bimanese Traditional Healing Practices in Patients with Hypertension in West Nusa Tenggara, Indonesia - Martiningsih, Martiningsih; Enie Novieastari; Astuti Yuni Nursasi; Ella Nurlaella Hadi (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2026)
Background: Incorporating cultural factors into nursing care can support the achievement of therapeutic goals. The use of traditional medicine alongside conventional treatment has gained attention in managing hypertension, especially in culturally diverse settings. Purpose: This study aims to explore the medication practices of patients with hypertension from a nursing perspective, emphasizing cultural influences and traditional medicine use. Methods: Employing a qualitative ethnographic design, the research was conducted at three public health centers in rural and urban Bima, Sumbawa Island, West Nusa Tenggara, from February to August 2024. Sixteen patients with hypertension, purposively selected via snowball sampling, participated through in-depth interviews and participant observation. Data analysis involved thematic analysis and triangulation, with validation from informants and experts. Results: Findings reveal that patients often combine prescribed antihypertensive medications with traditional remedies. Three main themes emerged. The first, cultural care practices in medication, includes six subthemes: oral traditional medicine, traditional body scrubs for warming, Bimanese munching-spraying medicine, and treatments applied to the head. The second theme highlights the combination of Bimanese traditional treatments with hypertension medication, divided into two subthemes. The third emphasizes belief in the effectiveness of Bimanese treatments. These practices are deeply rooted in local cultural beliefs and traditions. Conclusions: Recognizing and integrating traditional treatments into nursing care can improve medication adherence among hypertensive patients. Respecting cultural practices and fostering trust in traditional medicine are essential for culturally competent care. Healthcare providers should consider these factors to enhance treatment outcomes and patient satisfaction.